2019
DOI: 10.3390/md17020102
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anti-Candida Activity of Bengazole A in the Presence of Bengamide A

Abstract: Bengazoles A–G from the marine sponge Jaspis sp. exhibit potent in vitro antifungal activity against Candida spp. and other pathogenic fungi. The mechanism of action (MOA) of bengazole A was explored in Candida albicans under both liquid culture and surface culture on Mueller-Hinton agar. Pronounced dose-dependent synergistic antifungal activity was observed with bengazole A in the presence of bengamide A, which is also a natural product from Jaspis sp. The MOA of bengazole A was further explored by monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Bengamide also appeared in LC/MS analyses of the study from Zeyad et al (2022), previously quoted, but the authors did not present any observations about this compound. However, studies from Jamison et al (2019) observed the potent antifungal activity of the bengamide associated with bengazole against Candida. The action mechanism was methionine aminopeptidases (MetAPs) inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Bengamide also appeared in LC/MS analyses of the study from Zeyad et al (2022), previously quoted, but the authors did not present any observations about this compound. However, studies from Jamison et al (2019) observed the potent antifungal activity of the bengamide associated with bengazole against Candida. The action mechanism was methionine aminopeptidases (MetAPs) inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the bengazoles, which are the second most common secondary metabolites found in Jaspis species (Figure 5), stand out for their antifungal activity against Candida albicans [50,51], displaying comparable values of inhibition with amphotericin B and with a similar mode of action [52]. In a recent study conducted by Molinski et al [53], it was found a synergistic activity of a mixture of bengamide A (1) and bengazoles A-G (59a-g). In fact, it was observed that while pure bengazoles presented a MIC value of 1 µM against C. albicans at 0.5 µg/disk, inducing a zone of inhibition of 9-10 mm, a sample containing a mixture of bengazoles and bengamides produced a larger inhibition zone of 40 mm.…”
Section: Antifungal Activities Of the Bengamidesmentioning
confidence: 96%